Answer:
x = 180 - [(180 - 3x) + (180 - 2x)]
Step-by-step explanation:
Start off by finding the angles of the triangle
Angle F = 180 - 3x
The angle across from I (which I will call I) = 180 - 2x
Angle G = 180 - (F + I)
Now that we know what G is, we know what x is because the Alternate Exterior Angles Theorem states that if a pair of parallel lines are cut by a transversal, then the alternate exterior angles are congruent. So pretty much X = G
Therefore x = 180 - (F + I) or otherwise said as:
x = 180 - [(180 - 3x) + (180 - 2x)]
I hope this is helpful :)